Analyzing the Role of ICT Sector to the National Economic Structural Change: the Case of Indonesia - Zuhdi, Ubaidillah; Utomo, Dhanan Sarwo; Alamanda, Dini Turipanam (SBM ITB, 2011)
The one of technology which has the most significant role in human lives is Information and Communication Technology (ICT). This study is conducted to analyze the role of ICT in economic aspect of Indonesia from 1990 through 2005. The term of economic aspect used in this study is refers to the national economic structural changes. Structural decomposition analysis, the one of input-output analysis method, is used in this study. Analysis from macroscopic view shows that ICT sectors had not significant role in national economic structure changes of Indonesia between 1990 and 2005. In order to enhance economic growth of Indonesia, Indonesia government should improve the coherence and predictability and credibility aspect of ICT regulations.Keywords: ICT, structural decomposition analysis, macroscopic view, ICT regulations Â